Neonatal (and Infant) Coarctation of the Aorta: Management Challenges - Rao PS (Dove Medical Press, 2020)
P Syamasundar Rao Department of Pediatrics, University of Texas-Houston McGovern Medical School, Children’s Memorial Hermann Hospital, Houston, TX, USACorrespondence: P Syamasundar RaoEmeritus Chief of Pediatric Cardiology, UT-Houston McGovern Medical School, 6410 Fannin, UTPB Suite # 425, Houston, TX 77030, USATel +1 713-500-5738Fax +1 713-500-5751Email P.Syamasundar.Rao@uth.tmc.eduAbstract: Surgical correction of coarctation of the aorta was described in the mid-1940s and balloon angioplasty was introduced in the early 1980s. Several types of surgical methods were devised to treat native coarctation, but eventually, resection and end-to-end anastomosis became a standard approach with the use of extended end-to-end anastomosis for babies with hypoplasia of the isthmus and/or transverse aortic arch. Balloon angioplasty was considered as a substitute for surgical correction and was so used for some time, but because of high rate of recurrence in the neonate and young infant, most centers have reverted back to surgical correction as a primary mode of treatment of aortic coarctation in the neonate. Further research into feasibility of using stents in the management of coarctation in neonates and young infants are necessary. It is generally agreed that balloon angioplasty is the treatment of choice for post-surgical aortic recoarctations.Keywords: coarctation of the aorta, balloon angioplasty, surgical correction, neonate, stents, post-surgical recoarctation